2006
DOI: 10.1080/09638280500190631
|View full text |Cite
|
Sign up to set email alerts
|

A long-term population-based clinical and morbidity profile of Angelman syndrome in Western Australia: 1953–2003

Abstract: The estimated incidence was low compared to other reports, as was the proportion of IQ < 40. AS cases required substantial levels of medical care, especially those who were epileptic. An increase in the future numbers of AS patients needing sheltered accommodation is predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 31 publications
4
55
0
2
Order By: Relevance
“…Sustained seizure-freedom following epilepsy in childhood has been found in four of five patients with a 15q11-q13 deletion followed up longitudinally until the age of 30 years or more (Uemura et al, 2005). Other studies, however, have shown that epilepsy can persist or reappear in adulthood (Moncla et al, 1999;Thomson et al, 2006).…”
Section: Natural History Of the Seizure Disordermentioning
confidence: 97%
“…Sustained seizure-freedom following epilepsy in childhood has been found in four of five patients with a 15q11-q13 deletion followed up longitudinally until the age of 30 years or more (Uemura et al, 2005). Other studies, however, have shown that epilepsy can persist or reappear in adulthood (Moncla et al, 1999;Thomson et al, 2006).…”
Section: Natural History Of the Seizure Disordermentioning
confidence: 97%
“…Despite the range of symptoms, individuals with AS are often recognized by a generally happy disposition [18,19]. AS affects between 1 in 15,000 and 1 in 40,000 individuals [20,21]. Some studies have provided support to indicate that approximately 60% of patients may also be diagnosed with autism [22].…”
Section: Angelman Syndromementioning
confidence: 99%
“…Die eigenen Erfahrungen bei Patienten mit AS beruhen vorrangig auf Narkosen für oralchirurgische Eingriffe bei 6 von 7 S-Patienten, die sich im Rahmen einer Spezialsprechstunde für Menschen mit Behinderungen vorstellten. Oralchirurgische Eingriffe sind die häufigsten operativen Eingriffe bei ASPatien ten [45].…”
Section: Narkosen Bei Patienten Mit Angelman-syndrom In Berlinunclassified